Psychological and hormonal effects of socio-emotional learning in adolescents: a randomized controlled trial - Diana Prata; Susana Fonseca; Ana Ramos (Humanities & Social Sciences Communications)
Abstract Socio-emotional learning (SEL) is thought to increase children and youth’s social competencies such as empathy, however it has not been widely integrated in educational settings. This may be due to a lack of randomized-controlled trial (RCT) designs and objective and quantitative measurements, including of its neurobiological underpinnings, particularly in adolescence. This study examined the effect of a 1-week SEL intervention, and of a group-bonding task within it, on salivary oxytocin levels, and on the Multifaceted Empathy Test, using an RCT design and a repeated measures between subjects ANOVA, in 88 adolescents (35 female and 53 male). We found that salivary oxytocin was increased by performing the group-bonding task (p = 0.007, η²p = 0.089), but the 1-week intervention as whole did not augment this increase. The intervention increased emotional empathy, at a statistical trend level, in females. Lastly, an emotional empathy increase (from the first time to second time performing the group-bonding task) was positively correlated with an oxytocin increase (r = 0.235, p = 0.033), regardless of intervention. These findings point to a positive impact of SEL on emotional empathy, and of group-bonding tasks on endogenous oxytocin release, albeit preliminarily; with further replicatory research warranted.